Система інформаційної підтримки прийняття оперативних управлінських рішень - Самойленко, О.А. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2009)
The paper considers the main aspects of developing a combined system for information support of managerial decisions. A corresponding software is developed. Functional capabilities and features of main parts of the system are presented.